ESL learners' perceptions of using High-Variability Phonetic Training (HVPT) through YouGlish to improve pronunciation skills - Rizgar Qasim Mahmood (Australian Journal of Applied Linguistics)
This study explores ESL learners' perceptions of using high-variability phonetic training (HVPT) through YouGlish to improve pronunciation skills. Data were collected through an online questionnaire completed by 70 upper-intermediate level ESL learners and semi-structured interviews with 20 learners. The collected data were analyzed statistically and thematically. The results revealed that the majority of learners had significantly positive attitudes towards using this online tool. They reported that YouGlish assisted them in accurately learning how to pronounce words and phrases from a variety of accents, including Australian, British, and American. Additionally, while learners had positive perceptions of using HVPT and YouGlish for pronunciation improvement, they emphasized the critical role of teachers in providing explicit corrective feedback and additional clarifications. Furthermore, the participants also reported some drawbacks of YouGlish. This study offers both theoretical and pedagogical implications for language learning and teaching.